Aramaic Inscriptions and Documents of the Roman Period: Aramaic Inscriptions and Documents of the Roman Period - Healey, John F. (Textbook of Syrian Semitic Inscriptions, 2009)
In the first centuries AD, although much of the Near East was ruled by Rome, the main local language was Aramaic, and the people who lived inside or on the fringes of the area controlled by the Romans frequently wrote their inscriptions and legal documents in their own local dialects of this language. This book introduces these fascinating early texts to a wider audience, by presenting a representative sample, comprising eighty inscriptions and documents in the following dialects:Nabataean, Jewish, Palmyrene, Syriac, and Hatran. Detailed commentaries on the texts are preceded by chapters on hi